2014
DOI: 10.3349/ymj.2014.55.6.1556
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Problems and Clinical Outcomes of Children with Psychogenic Non-Epileptic Seizures

Abstract: PurposeOur purpose was to investigate psychological problems and clinical outcomes in children with psychogenic non-epileptic seizures (PNES).Materials and MethodsWe retrospectively reviewed the data of 25 patients who were diagnosed with PNES between 2006 and 2012.ResultsTwenty-five children with PNES, aged 8 to 19 years (mean 13.82), were referred to psychiatrists for psychiatric assessment. On their initial visit, 72% of patients had comorbid psychological problems, including depression, anxiety, conduct di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
1
18
0
2
Order By: Relevance
“…We did not control for parental social factors. It is likely that this would be of relevance since PNES is probably influenced by social rank [39]. However, the data here were insufficiently complete to enable the familiar analysis that would ideally be required.…”
Section: Discussionmentioning
confidence: 95%
“…We did not control for parental social factors. It is likely that this would be of relevance since PNES is probably influenced by social rank [39]. However, the data here were insufficiently complete to enable the familiar analysis that would ideally be required.…”
Section: Discussionmentioning
confidence: 95%
“…In the pediatric population, attention deficits are associated with PNES. Studies have reported that 7% to 28% of children with PNES are jointly diagnosed with ADHD (Rawat et al, 2015; Yi, Kim, Lee, Cheon, & Kang, 2014). However, the comorbidity of ADHD and PNES in adults has not been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to adolescents with epilepsy and healthy controls, a history of traumatising/stressful events, sexual and physical abuse was found to be significantly more common in adolescents with PNES [19]. Yi et al [20] reported that histories of interpersonal or familial distress were seen as precipitants of PNES in their sample. Such traumatic histories were also classified as potential precipitants to PNES onset in the study conducted by Irwin, Edwards and Robinson (2000), with experiences of domestic tension, bullying, dysfunctional maternal relationships, violence, and physical and sexual abuse being reported.…”
Section: Distress and The Social And Emotional Impact Of Pnesmentioning
confidence: 93%